2010
DOI: 10.3844/jssp.2010.50.54
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Perceived Fitness Level of Exercise Partner on Intensity of Exertion

Abstract: Problem statement: Social comparison theory was used to examine if exercising with a research confederate posing as either high fit or low fit would increase the exertion in exercising. Approach: 91 college students were randomly assigned to one of three conditions: Biking alone, biking with a high fit confederate, or biking with a low fit confederate. All participants were instructed to complete 20 min of exercise at 60-70% of their maximum target heart rate. Results: Results indicated that participants in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 23 publications
3
23
0
Order By: Relevance
“…Similar to other studies (Feltz, Kerr, & Irwin, 2011;Irwin, Scorniaenchi, Kerr, Eisenmann, & Feltz, 2012;Plante et al, 2010;Winchester et al, 2012), the peer-based aspect of the program not only encouraged ongoing program participation, but also increased patients' motivation to exercise harder during each session. It could be possible that receiving positive encouragement from others enhanced patients' belief in their ability to exercise (i.e., self-efficacy) and that this led to increases in effort (Hutchinson, Sherman, Martinovic, & Tenenbaum, 2008).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Similar to other studies (Feltz, Kerr, & Irwin, 2011;Irwin, Scorniaenchi, Kerr, Eisenmann, & Feltz, 2012;Plante et al, 2010;Winchester et al, 2012), the peer-based aspect of the program not only encouraged ongoing program participation, but also increased patients' motivation to exercise harder during each session. It could be possible that receiving positive encouragement from others enhanced patients' belief in their ability to exercise (i.e., self-efficacy) and that this led to increases in effort (Hutchinson, Sherman, Martinovic, & Tenenbaum, 2008).…”
Section: Discussionmentioning
confidence: 54%
“…In this regard, it is possible that having another person exercise next to patients created a sense of healthy competition, and this nurtured the patients' desire to do better. In support of this proposition, researchers have shown that exercise performance increases in competitive settings (Plante et al, 2010;Rhea, Landers, Alvar, & Arent, 2003). Thus, while competitive environments can decrease intrinsic motivation (Frederick-Recascino & Schuster-Smith, 2003), it appears that it is not always demotivating, and can be motivating in some circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Group dynamics involve a participant joining an exercise class that builds social cohesion with other members of the class and has consistently been shown to improve adherence [69–71]. Other benefits of group exercise may include adopting positive exercise behaviors of the group [72], and reduced stress [73]. Sample recreational activities include tennis/wheelchair tennis, golf with or without an accessible golf cart, various forms of adapted dance, hiking, handcyling/cycling and warm-water aquatics classes, such as volleyball or tai chi.…”
Section: The Transformative Exercise Frameworkmentioning
confidence: 99%
“…People engage in exercise for a variety of reasons, including perceived health benefits and social enjoyment (Ogden, 2012;Plante et al, 2010). A person's perceptions and beliefs about exercise may determine their engagement with exercise (Whaley and Schrider, 2005).…”
Section: Introductionmentioning
confidence: 99%